Resin composition

A resin composition with epoxy resin, active ester, inorganic filler, and biphenyl-containing (meth)acrylic ester addresses low smear removability and adhesion issues in printed wiring boards, offering improved performance and dielectric properties.

JP7605087B2Active Publication Date: 2024-12-24AJINOMOTO CO INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021181859
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-08
Publication Date
2024-12-24
Estimated Expiration
2041-11-08

AI Technical Summary

Technical Problem

Existing resin compositions with high concentrations of active ester compounds and inorganic fillers for insulating layers in printed wiring boards suffer from low smear removability, plating adhesion, and metal foil adhesion, which are crucial for manufacturing high-quality printed wiring boards.

Method used

A resin composition comprising specific amounts of epoxy resin, active ester compound, inorganic filler, and (meth)acrylic ester with a biphenyl skeleton, which enhances smear removability, plating adhesion, and metal foil adhesion while maintaining a low dielectric loss tangent.

Benefits of technology

The composition provides a cured product with improved smear removability, plating adhesion, and metal foil adhesion, along with a low dielectric loss tangent, suitable for forming insulating layers in printed wiring boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605087000001
    Figure 0007605087000001
  • Figure 0007605087000002
    Figure 0007605087000002
  • Figure 0007605087000003
    Figure 0007605087000003
Patent Text Reader

Abstract

To provide a resin composition capable of giving a cured product excellent in all of smear removability, plating adhesion, and metal foil adhesion.SOLUTION: The resin composition contains (A) an epoxy resin, (B) an active ester compound, (C) an inorganic filler, and (D) a (meth)acrylate having a biphenyl skeleton. The content of the active ester compound (B) is 10 mass% or more based on 100 mass% of a nonvolatile component in the resin composition. The content of the inorganic filler (C) is 60 mass% or more based on 100 mass% of the nonvolatile component in the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. [Background technology]

[0002] A known manufacturing technique for printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked. In the build-up method, the insulating layers are generally formed from a cured product obtained by curing a resin composition (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-23714 A Summary of the Invention [Problem to be solved by the invention]

[0004] The cured product contained in the insulating layer is required to have a low dielectric tangent. One method for obtaining a cured product with a low dielectric tangent is to blend an active ester compound and an inorganic filler in a resin composition at a high concentration. However, when a resin composition containing an active ester compound and an inorganic filler in a high concentration is used, the smear removability, plating adhesion, and metal foil adhesion tend to all be low.

[0005] Specifically, when an insulating layer is formed by a cured product of a resin composition, holes such as via holes and through holes may be formed in the insulating layer. When such holes are formed in the insulating layer, smears may be formed in the holes as resin residues. In general, this smear needs to be removed. Smear removal is often performed using chemicals. However, when a resin composition containing a high concentration of an active ester compound and an inorganic filler is used, the smear removal tends to be low.

[0006] In addition, when a conductor layer is formed on an insulating layer, the conductor layer may be formed by plating. However, when a resin composition containing an active ester compound and an inorganic filler at a high concentration is used, the adhesion between the insulating layer and the conductor layer formed by plating tends to be low.

[0007] Furthermore, in the manufacturing process of a printed wiring board, an insulating layer is sometimes formed on a conductor layer as a base using a resin composition. The conductor layer as the base is usually a metal foil at the time of forming the insulating layer. Therefore, the insulating layer is required to have excellent adhesion to the metal foil as the base. However, when a resin composition containing a high concentration of an active ester compound and an inorganic filler is used, the adhesion between the insulating layer and the metal foil as the base tends to be low.

[0008] The present invention has been made in view of the above problems, and has an object to provide: a resin composition capable of giving a cured product excellent in all of smear removability, plating adhesion, and metal foil adhesion; a cured product of the resin composition; a sheet-like laminate material containing the resin composition; a resin sheet having a resin composition layer formed from the resin composition; a printed wiring board provided with an insulating layer including a cured product of the resin composition; and a semiconductor device provided with the printed wiring board. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result, have found that a resin composition containing, in combination, (A) an epoxy resin, a specific amount of (B) an active ester compound, a specific amount of (C) an inorganic filler, and (D) a (meth)acrylic acid ester having a biphenyl skeleton can solve the above-mentioned problems, thereby completing the present invention. That is, the present invention includes the following.

[0010] [1] A resin composition comprising (A) an epoxy resin, (B) an active ester compound, (C) an inorganic filler, and (D) a (meth)acrylic acid ester having a biphenyl skeleton, Resin Composition thing the content of the active ester compound (B) is 10% by mass or more when the non-volatile components therein are taken as 100% by mass, Resin Composition thing The resin composition has an inorganic filler content of 60 mass % or more, based on 100 mass % of non-volatile components therein. [2] The resin composition according to [1], wherein the (D) (meth)acrylic acid ester having a biphenyl skeleton includes a compound containing an ether structure. [3] The resin composition according to [1] or [2], wherein the (D) (meth)acrylic acid ester having a biphenyl skeleton includes a compound represented by the following formula (D1): [ka] (In formula (D1), R 11 each independently represents a hydrogen atom or a methyl group; R 12 each independently represents a divalent aliphatic hydrocarbon group, m1 represents an integer of 0 to 5; n1 represents an integer from 0 to 6; R 21 each independently represents a hydrogen atom or a methyl group; R 22 each independently represents a divalent aliphatic hydrocarbon group, m2 represents an integer of 0 to 5; n2 represents an integer of 0 to 6. However, m1+m2 is 1 or greater.) [4] Resin composition thing The resin composition according to any one of [1] to [3], wherein the content of the (D) (meth)acrylic acid ester having a biphenyl skeleton is 0.5% by mass or more and 25% by mass or less, based on 100% by mass of non-volatile components in the resin composition. [5] The resin composition according to any one of [1] to [4], comprising one or more types of (E) curing agents selected from the group consisting of phenol-based curing agents and carbodiimide-based curing agents. [6] The resin composition according to any one of [1] to [5], further comprising (F) a curing accelerator. [7] The resin composition according to any one of [1] to [6], which contains a thermoplastic resin (G). [8] The resin composition according to any one of [1] to [7], which is for forming an insulating layer. [9] A cured product of the resin composition according to any one of [1] to [8].

[10] A sheet-like laminate material containing the resin composition according to any one of [1] to [8].

[11] A resin sheet comprising a support and a resin composition layer formed on the support from the resin composition according to any one of [1] to [8].

[12] A printed wiring board having an insulating layer containing a cured product of the resin composition according to any one of [1] to [8].

[13] A semiconductor device comprising the printed wiring board according to

[12] . Effect of the Invention

[0011] According to the present invention, there can be provided a resin composition capable of giving a cured product excellent in all of smear removability, plating adhesion, and metal foil adhesion; a cured product of the resin composition; a sheet-like laminate material containing the resin composition; a resin sheet having a resin composition layer formed from the resin composition; a printed wiring board comprising an insulating layer including a cured product of the resin composition; and a semiconductor device comprising the printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims and their equivalents.

[0013] In the following description, the term "(meth)acrylic acid ester" includes acrylic acid ester, methacrylic acid ester, and combinations thereof, unless otherwise specified. In the following description, the term "(meth)acryloyl group" includes acryloyl group, methacryloyl group, and combinations thereof, unless otherwise specified. In the following description, the term "(meth)acryloyloxy group" includes acryloyloxy group, methacryloyloxy group, and combinations thereof, unless otherwise specified. In the following description, the term "(meth)acrylate" includes acrylate, methacrylate, and combinations thereof, unless otherwise specified.

[0014] [1. Overview of resin composition] A resin composition according to one embodiment of the present invention includes a combination of (A) an epoxy resin, a specific amount of (B) an active ester compound, a specific amount of (C) an inorganic filler, and (D) a (meth)acrylic acid ester having a biphenyl skeleton. This resin composition can provide a cured product that is excellent in smear removal, plating adhesion, and metal foil adhesion. In addition, this cured product can usually have a low dielectric tangent. Furthermore, this cured product can usually have a small surface roughness after roughening treatment. This cured product can be suitably used, for example, as a material for an insulating layer of a printed wiring board.

[0015] The present inventors speculate that the mechanism by which the cured product of the resin composition according to the present embodiment provides the above-mentioned excellent advantages is as follows, however, the technical scope of the present invention is not limited by the mechanism described below.

[0016] A cured product of a conventional resin composition containing an epoxy resin, a predetermined amount or more of an active ester compound, and a predetermined amount or more of an inorganic filler can usually have a low dielectric tangent. However, the cured product of the resin composition generally tends to have poor smear removability, plating adhesion, and metal foil adhesion.

[0017] In contrast, the resin composition according to the present embodiment contains (A) an epoxy resin, a specific range of the amount of (B) an active ester compound, a specific range of the amount of (C) an inorganic filler, and (D) a (meth)acrylic acid ester having a biphenyl skeleton in combination. The (meth)acrylic acid ester having a biphenyl skeleton as the (D) component may be hereinafter referred to as the "specific (meth)acrylic acid ester". The carbon-carbon unsaturated bond (ethylenic unsaturated bond) of the (meth)acryloyl group contained in the (D) specific (meth)acrylic acid ester may cause a radical polymerization reaction when the resin composition is cured, so that the (D) specific (meth)acrylic acid esters may bond to each other in the cured product. The bond between the (D) specific (meth)acrylic acid esters contained in this cured product can be easily oxidized and cut by an oxidizing agent used to remove smears. Therefore, the removal of the cured product by the oxidizing agent can be promoted, and the smear removability is improved.

[0018] In addition, since the biphenyl skeleton contained in the specific (meth)acrylic acid ester (D) has high rigidity, the action of the specific (meth)acrylic acid ester (D) containing the biphenyl skeleton can increase the mechanical strength of the cured product of the resin composition. Therefore, the resistance of the cured product to stress can be increased. Therefore, peeling (interlayer peeling) accompanied by destruction of the cured product can be suppressed, and plating adhesion and metal foil adhesion can be improved.

[0019] Furthermore, the radical polymerization reaction of the specific (meth)acrylic acid ester (D) does not usually generate polar groups such as hydroxyl groups. Therefore, even if the specific (meth)acrylic acid ester (D) is contained, the polarity of the cured product can be low. Therefore, the cured product of the resin composition can usually have a low dielectric loss tangent.

[0020] In addition, the (D) specific (meth)acrylic acid ester having a biphenyl skeleton can have excellent affinity with the (A) epoxy resin and the (B) active ester compound. Therefore, phase separation of the resin components such as the (A), (B) and (D) components in the resin composition is suppressed. If the resin components undergo large phase separation, large phase domains are formed in the cured product, and detachment occurs for each phase domain during roughening treatment, which may increase the surface roughness. However, in the resin composition according to this embodiment, the phase separation of the resin components is suppressed, so the formation of large phase domains is suppressed. Therefore, it is usually possible to have a small surface roughness after roughening treatment.

[0021] [2. (A) Epoxy resin] The resin composition according to the present embodiment contains an epoxy resin (A) as component (A). The epoxy resin (A) can be a curable resin having an epoxy group.

[0022] Examples of the (A) epoxy resin include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, and phenolphthalimidine type epoxy resins. The (A) epoxy resin may be used alone or in combination of two or more kinds.

[0023] From the viewpoint of obtaining a cured product having excellent heat resistance, the (A) epoxy resin preferably contains an epoxy resin containing an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles. Examples of epoxy resins containing an aromatic structure include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, bisxylenol type epoxy resins, glycidylamine type epoxy resins having an aromatic structure, glycidyl ester type epoxy resins having an aromatic structure, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins having an aromatic structure, epoxy resins having a butadiene structure having an aromatic structure, alicyclic epoxy resins having an aromatic structure, heterocyclic epoxy resins, spiro ring-containing epoxy resins having an aromatic structure, cyclohexane dimethanol type epoxy resins having an aromatic structure, naphthylene ether type epoxy resins, trimethylol type epoxy resins having an aromatic structure, and tetraphenylethane type epoxy resins having an aromatic structure.

[0024] The resin composition preferably contains, as the (A) epoxy resin, an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the (A) epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0025] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only liquid epoxy resins as the epoxy resin, or may contain only solid epoxy resins, or may contain a combination of liquid epoxy resins and solid epoxy resins.

[0026] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0027] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred.

[0028] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" ( glycidylamine type epoxy resin); ADEKA's "EP-4088S" (dicyclopentadiene type epoxy resin); Nippon Steel Chemical & Material Chemical's "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); Nagase Chemtex's "EX-721" (glycidyl ester type epoxy resin); Daicel's "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton); Daicel's "PB-3600", Nippon Soda's "JP-100" and "JP-200" (epoxy resin having a butadiene structure); Nippon Steel Chemical & Material's "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin), etc. These may be used alone or in combination of two or more types.

[0029] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0030] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.

[0031] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-7311" manufactured by DIC Corporation. , "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V", "ESN4 100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "Y Examples of epoxy resins include "X7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.

[0032] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (A) epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably 20:1 to 1:20, more preferably 10:1 to 1:10, and particularly preferably 7:1 to 1:7.

[0033] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 3,000 g / eq., further preferably 80 g / eq. to 2,000 g / eq., and particularly preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent represents the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0034] The weight average molecular weight (Mw) of the epoxy resin (A) is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0035] The content of the epoxy resin (A) in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 4% by mass or more, and is preferably 25% by mass or less, more preferably 20% by mass or less, particularly preferably 10% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. When the amount of the epoxy resin (A) is within the above range, the smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0036] The content of the epoxy resin (A) in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and preferably 70% by mass or less, more preferably 50% by mass or less, particularly preferably 30% by mass or less, based on the resin components in the resin composition being 100% by mass. The resin components of the resin composition refer to the non-volatile components of the resin composition excluding the inorganic filler (C). When the amount of the epoxy resin (A) is within the above range, the smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0037] [3. (B) Active ester compounds] The resin composition according to the present embodiment contains an active ester compound (B) as the component (B) in a specific range of content. The active ester compound (B) can function as an epoxy resin curing agent that reacts with the epoxy resin (A) to cure the resin composition. The active ester compound (B) may be used alone or in combination of two or more.

[0038] As the (B) active ester compound, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0039] Specifically, the (B) active ester compound is preferably a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, or an active ester compound containing a benzoylated product of phenol novolac, and more preferably at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.

[0040] (B) Commercially available active ester compounds include, for example, active ester compounds containing a dicyclopentadiene-type diphenol structure such as "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-8150-60T", and "EXB-81 Examples of such active ester compounds include "EXB-9416-70BK", "HPC-8150-60T", "HPC-8150-62T", and "EXB-8" (manufactured by DIC Corporation); an active ester compound containing phosphorus, such as "EXB9401" (manufactured by DIC Corporation); an active ester compound which is an acetylated product of phenol novolac, such as "DC808" (manufactured by Mitsubishi Chemical Corporation); active ester compounds which are benzoylated products of phenol novolac, such as "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation); and an active ester compound containing a styryl group and a naphthalene structure, such as "PC1300-02-65MA" (manufactured by Air Water Corporation).

[0041] The active ester group equivalent of the (B) active ester compound is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and further preferably 100 g / eq. to 300 g / eq. The active ester group equivalent represents the mass of the active ester compound per equivalent of the active ester group.

[0042] When the number of epoxy groups in the (A) epoxy resin is taken as 1, the number of active ester groups in the (B) active ester compound is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 1.0 or more, and preferably 5.0 or less, more preferably 4.0 or less, and particularly preferably 3.0 or less. The "number of epoxy groups in the (A) epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the (A) epoxy resin present in the resin composition by the epoxy equivalent. The "number of active ester groups in the (B) active ester compound" refers to the total value obtained by dividing the mass of the non-volatile components of the (B) active ester compound present in the resin composition by the active ester group equivalent.

[0043] The content of the (B) active ester compound in the resin composition is usually 10% by mass or more, preferably 11% by mass or more, more preferably 12% by mass or more, even more preferably 13% by mass or more, particularly preferably 14% by mass or more, and is preferably 35% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less, particularly preferably 20% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the amount of the (B) active ester compound is within the above range, the smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0044] The content of the (B) active ester compound in the resin composition is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, particularly preferably 60% by mass or less, when the resin component in the resin composition is taken as 100% by mass. When the amount of the (B) active ester compound is within the above range, smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0045] [4.(C) Inorganic filler] The resin composition according to the present embodiment contains the inorganic filler (C) in a content within a specific range. The inorganic filler (C) is usually contained in the resin composition in the form of particles.

[0046] (C) An inorganic compound is used as the material of the inorganic filler. (C) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica and alumina are preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferred as the silica. The (C) inorganic filler may be used alone or in combination of two or more kinds.

[0047] (C) Commercially available inorganic fillers include, for example, "UFP-30" manufactured by Denka Chemical Industry Co., Ltd.; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denka Company; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; and "DAW-03" and "FB-105FD" manufactured by Denka Company, Ltd.

[0048] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (C) inorganic filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, particularly preferably 0.2 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 2 μm or less, particularly preferably 1 μm or less.

[0049] (C) The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is prepared on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample can be measured by using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, measuring the particle size distribution of the inorganic filler on a volume basis using a flow cell method, and calculating the average particle size as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0050] The specific surface area of ​​the (C) inorganic filler is preferably 0.1 m from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 / g or more, preferably 100m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 The specific surface area of ​​the inorganic filler can be measured by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0051] (C) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.

[0052] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0053] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a specific range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably with 0.2% to 3% by mass of the surface treatment agent, and even more preferably with 0.3% to 2% by mass of the surface treatment agent.

[0054] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition, it is more preferable that the content is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0055] (C) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0056] The content of the (C) inorganic filler in the resin composition is preferably 60% by mass or more, more preferably 65% ​​by mass or more, particularly preferably 70% by mass or more, and is preferably 86% by mass or less, more preferably 82% by mass or less, particularly preferably 78% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. When the amount of the (C) inorganic filler is within the above range, the smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0057] [5. (D) (Meth)acrylic acid esters having a biphenyl skeleton] The resin composition according to the present embodiment contains, as the component (D), (D) a (meth)acrylic acid ester having a biphenyl skeleton (that is, (D) a specific (meth)acrylic acid ester).

[0058] The (D) specific (meth)acrylic acid ester contains a (meth)acryloyloxy group in its molecule. The carbon-carbon unsaturated bond (ethylenic unsaturated bond) contained in the (meth)acryloyloxy group can usually cause a radical polymerization reaction when the resin composition is cured. The number of (meth)acryloyloxy groups contained in the molecule of the (D) specific (meth)acrylic acid ester may be 1 or 2 or more. The specific number of (meth)acryloyloxy groups contained in the molecule of the (D) specific (meth)acrylic acid ester is preferably 1 or more, and is preferably 6 or less, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 2 or less.

[0059] The (D) specific (meth)acrylic acid ester has a biphenyl skeleton in its molecule. The number of biphenyl skeletons contained in the (D) specific (meth)acrylic acid ester molecule may be 2 or more, but is usually 1. The (meth)acryloyloxy group may be bonded directly or indirectly via a linking group to the benzene ring of this biphenyl skeleton. When the (D) specific (meth)acrylic acid ester has two or more (meth)acryloyloxy groups, the (meth)acryloyloxy group may be bonded to only one of the two benzene rings of the biphenyl skeleton, but it is preferable that the (meth)acryloyloxy group is bonded to each of the two benzene rings of the biphenyl skeleton.

[0060] The (D) specific (meth)acrylic acid ester preferably further contains an ether structure in combination with the (meth)acryloyloxy group and the biphenyl skeleton. Therefore, the (D) specific (meth)acrylic acid ester preferably contains a compound containing an ether structure. This ether structure does not include the ether structure contained in the (meth)acryloyloxy group. The number of ether structures contained in the molecule of the (D) specific (meth)acrylic acid ester containing an ether structure may be 1 or 2 or more. In addition, the ether structure is preferably contained in a linking group that links the (meth)acryloyloxy group and the benzene ring of the biphenyl skeleton. Furthermore, at least one oxygen atom contained in the ether structure is preferably directly bonded to the benzene ring.

[0061] Furthermore, the linking group linking the (meth)acryloyloxy group and the benzene ring of the biphenyl skeleton preferably contains a divalent aliphatic hydrocarbon group. Therefore, the specific (meth)acrylic acid ester (D) preferably contains a compound containing a linking group containing a divalent aliphatic hydrocarbon group. The divalent aliphatic hydrocarbon group is preferably a chain-like aliphatic hydrocarbon group, and may be linear or branched. In addition, the divalent aliphatic hydrocarbon group is preferably a saturated aliphatic hydrocarbon group. The number of carbon atoms of the divalent aliphatic hydrocarbon group is usually 1 or more, preferably 12 or less, more preferably 6 or less, even more preferably 4 or less, and particularly preferably 2 or less. Examples of preferred divalent aliphatic hydrocarbon groups include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, and a hexylene group.

[0062] As the (D) specific (meth)acrylic acid ester, in particular, a compound represented by the following formula (D1) is preferred. Therefore, the (D) specific (meth)acrylic acid ester preferably contains a compound represented by the following formula (D1), and more preferably contains only a compound represented by the following formula (D1).

[0063] [ka]

[0064] In formula (D1), R 11 Each of R independently represents a hydrogen atom or a methyl group. 21 each independently represents a hydrogen atom or a methyl group.

[0065] In formula (D1), R 12 Each of R independently represents a divalent aliphatic hydrocarbon group. 22 each independently represents a divalent aliphatic hydrocarbon group. As the divalent aliphatic hydrocarbon group, those within the above-mentioned range as the divalent aliphatic hydrocarbon group that may be contained in the linking group that links the (meth)acryloyloxy group to the benzene ring of the biphenyl skeleton can be used.

[0066] In formula (D1), m1 represents an integer of 0 to 5, preferably 0 or 1, and particularly preferably 1. In addition, in formula (D1), m2 represents an integer of 0 to 5, preferably 0 or 1, and particularly preferably 1, with the proviso that m1+m2 is 1 or more.

[0067] In formula (D1), n1's each independently represent an integer of 0 to 6. In addition, in formula (D1), n2's each independently represent an integer of 0 to 6. In detail, n1 and n2 are usually 0 or more, preferably 1 or more, and usually 6 or less, preferably 4 or less, more preferably 3 or less, and particularly preferably 2 or less. n1 and n2 may be the same or different.

[0068] Specific examples of the (D) specific (meth)acrylic acid ester include those represented by the following formulas (d1) to (d4): In the following formula, n represents an integer of 1 or more, preferably 1 to 2, and more preferably 1.

[0069] [ka]

[0070] (D) Examples of commercially available specific (meth)acrylic acid esters include "A-LEN-10" (a compound represented by formula (d1)) manufactured by Shin-Nakamura Chemical Co., Ltd. and "A-BP-2EO" (a compound represented by formula (d3)) manufactured by Honshu Chemical Industry Co., Ltd.

[0071] The (D) specific (meth)acrylic acid ester may be used alone or in combination of two or more kinds.

[0072] Mass W of epoxy resin (A) in the resin composition A and (D) the mass W of the specific (meth)acrylic acid ester. D Mass ratio W D / W Ais preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, particularly preferably 0.7 or more, and is preferably 10 or less, more preferably 5.0 or less, even more preferably 2.0 or less, particularly preferably 1.0 or less. D / W A When the value is within the above range, the plating adhesion and the metal foil adhesion can be effectively increased, and furthermore, the dielectric tangent can usually be effectively reduced.

[0073] Mass W of the active ester compound (B) in the resin composition B and (D) the mass W of the specific (meth)acrylic acid ester. D Mass ratio W D / W B is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.10 or more, particularly preferably 0.15 or more, and is preferably 2.0 or less, more preferably 1.5 or less, even more preferably 1.0 or less, particularly preferably 0.5 or less. D / W B When the value is within the above range, the plating adhesion and the metal foil adhesion can be effectively increased, and furthermore, the dielectric tangent can usually be effectively reduced.

[0074] The total mass W of the (A) epoxy resin and the (B) active ester compound in the resin composition A +W B and (D) the mass W of the specific (meth)acrylic acid ester. D Mass ratio W D / (W A +W B ) is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.10 or more, particularly preferably 0.20 or more, and is preferably 2.0 or less, more preferably 1.5 or less, even more preferably 1.0 or less, particularly preferably 0.5 or less. D / (W A +W B When the value of (a) is within the above range, the plating adhesion and the metal foil adhesion can be effectively increased, and furthermore, the dielectric tangent can usually be effectively reduced.

[0075] Mass W of (C) inorganic filler in the resin composition C and (D) the mass W of the specific (meth)acrylic acid ester. D Mass ratio W D / W C is preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, particularly preferably 0.03 or more, and is preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, particularly preferably 0.1 or less. D / W C When the value is within the above range, the plating adhesion and the metal foil adhesion can be effectively increased, and furthermore, the dielectric tangent can usually be effectively reduced.

[0076] The content of the (D) specific (meth)acrylic acid ester in the resin composition is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, particularly preferably 2.0% by mass or more, and is preferably 25% by mass or less, more preferably 20% by mass or less, particularly preferably 10% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. When the amount of the (D) specific (meth)acrylic acid ester is within the above range, the smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0077] The content of the (D) specific (meth)acrylic acid ester in the resin composition is preferably 2% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and is preferably 70% by mass or less, more preferably 40% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the resin component in the resin composition. When the amount of the (D) specific (meth)acrylic acid ester is within the above range, the smear removability, plating adhesion, metal foil adhesion, dielectric loss tangent, and surface roughness after roughening treatment can be particularly improved.

[0078] 6. (E) Optional Hardener The resin composition according to the present embodiment may further contain an optional curing agent (E) as an optional component in combination with the above-mentioned components (A) to (D). The optional curing agent (E) as the component (E) does not include those corresponding to the above-mentioned components (A) to (D). The optional curing agent (E) can function as an epoxy resin curing agent that reacts with the epoxy resin (A) to cure the resin composition, like the above-mentioned active ester compound (B). The optional curing agent (E) may be used alone or in combination of two or more kinds.

[0079] (E) The optional curing agent may be, for example, a phenol-based curing agent, a carbodiimide-based curing agent, an acid anhydride-based curing agent, an amine-based curing agent, a benzoxazine-based curing agent, a cyanate ester-based curing agent, or a thiol-based curing agent. Among these, it is preferable to use one or more curing agents selected from the group consisting of phenol-based curing agents and carbodiimide-based curing agents.

[0080] As the phenol-based curing agent, a curing agent having one or more, preferably two or more, hydroxyl groups bonded to an aromatic ring such as a benzene ring or a naphthalene ring in one molecule can be used. From the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferred. From the viewpoint of adhesion, a nitrogen-containing phenol-based curing agent is preferred, and a triazine skeleton-containing phenol-based curing agent is more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac resin is preferred. Specific examples of phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.

[0081] As the carbodiimide-based curing agent, a curing agent having one or more, preferably two or more, carbodiimide structures in one molecule can be used. Specific examples of the carbodiimide-based curing agent include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); poly(phenylenecarbodiimide), poly( Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide]. Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.

[0082] As the acid anhydride curing agent, a curing agent having one or more acid anhydride groups in one molecule can be used, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and benzophenonetetracarboxylic dianhydride. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include, for example, "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd.; "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.; and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley.

[0083] As the amine-based curing agent, a curing agent having one or more, preferably two or more, amino groups in one molecule can be used. As the amine-based curing agent, for example, aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. can be mentioned, among which aromatic amines are preferred. As the amine-based curing agent, primary amines or secondary amines are preferred, and primary amines are more preferred. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. Commercially available amine-based curing agents include, for example, "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd.; "Epicure W" manufactured by Mitsubishi Chemical Corporation; and "DTDA" manufactured by Sumitomo Seika Chemicals Co., Ltd.

[0084] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0085] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0086] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0087] The active group equivalent of the (E) optional curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The active group equivalent represents the mass of the curing agent per equivalent of the active group.

[0088] The content of the optional curing agent (E) in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 1.0% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0089] The content of the optional curing agent (E) in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.1% by mass or more, more preferably 1.0% by mass or more, and particularly preferably 5.0% by mass or more, and is preferably 50% by mass or less, more preferably 20% by mass or less, and particularly preferably 10% by mass or less, when the resin component in the resin composition is 100% by mass.

[0090] [7. (F) Curing accelerator] The resin composition according to the present embodiment may further contain a curing accelerator (F) as an optional component in combination with the above-mentioned components (A) to (E). The curing accelerator (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E). The curing accelerator (F) functions as a curing catalyst that accelerates the curing of the epoxy resin (A).

[0091] Examples of the (F) curing accelerator include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. Among these, imidazole-based curing accelerators are preferred. The (F) curing accelerators may be used alone or in combination of two or more.

[0092] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0093] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0094] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0095] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0096] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0097] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0098] The content of the (F) curing accelerator in the resin composition may be 0% by mass or more, and is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, particularly preferably 0.03% by mass or more, and is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0099] The content of the (F) curing accelerator in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more, and is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, and particularly preferably 1.0% by mass or less, based on the resin component in the resin composition being 100% by mass.

[0100] [8.(G) Thermoplastic resin] The resin composition according to the present embodiment may further contain a thermoplastic resin (G) as an optional component in combination with the above-mentioned components (A) to (F). The thermoplastic resin (G) as component (G) does not include those corresponding to the above-mentioned components (A) to (F).

[0101] Examples of the (G) thermoplastic resin include phenoxy resin, polyimide resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. The (G) thermoplastic resin may be used alone or in combination of two or more kinds.

[0102] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0103] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0104] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0105] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0106] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0107] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0108] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0109] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0110] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.

[0111] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.

[0112] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.

[0113] The weight average molecular weight (Mw) of the (G) thermoplastic resin is preferably greater than 5,000, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.

[0114] The content of the (G) thermoplastic resin in the resin composition may be 0% by mass or more, and is preferably 0.01% by mass or more, more preferably 0.10% by mass or more, and particularly preferably 0.20% by mass or more, and is preferably 5.0% by mass or less, more preferably 2.0% by mass or less, and particularly preferably 1.0% by mass or less, assuming that the non-volatile components in the resin composition are 100% by mass.

[0115] The content of the (G) thermoplastic resin in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.10% by mass or more, and particularly preferably 0.50% by mass or more, and is preferably 10% by mass or less, more preferably 5.0% by mass or less, and particularly preferably 3.0% by mass or less, assuming that the resin component in the resin composition is 100% by mass.

[0116] [9. (H) Radical polymerizable compounds] The resin composition according to the present embodiment may further contain (H) any radical polymerizable compound as an optional component in combination with the above-mentioned (A) to (G) components. The (H) radical polymerizable compound as the (H) component does not include those corresponding to the above-mentioned (A) to (G) components. The (H) radical polymerizable compound may be used alone or in combination of two or more types.

[0117] (H) radical polymerizable compound may have an ethylenically unsaturated bond. (H) radical polymerizable compound may have a radical polymerizable group such as an unsaturated hydrocarbon group such as an allyl group, a 3-cyclohexenyl group, a 3-cyclopentenyl group, a p-vinylphenyl group, a m-vinylphenyl group, or an o-vinylphenyl group; an α,β-unsaturated carbonyl group such as an acryloyl group, a methacryloyl group, or a maleimide group (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group); etc. (H) radical polymerizable compound preferably has two or more radical polymerizable groups.

[0118] Examples of the (H) radically polymerizable compound include (meth)acrylic radically polymerizable compounds, styrene radically polymerizable compounds, allyl radically polymerizable compounds, and maleimide radically polymerizable compounds.

[0119] The (meth)acrylic radical polymerizable compound is, for example, a compound having one or more, preferably two or more, acryloyl groups and / or methacryloyl groups. Examples of the (meth)acrylic radical polymerizable compound include cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonaphthalene di(meth)acrylate, 1,2-diphenylmethane di(meth)acrylate, 1,3-diphenylmethane di(meth)acrylate, 1,4-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,6-diphenylmethane di(meth)acrylate, 1,8-diphenylmethane di(meth)acrylate, 1,9-diphenylmethane ...5-diphenylmethane di(meth)acrylate, 1,6-diphenylmethane di(meth)acrylate, 1,3-diphenylmethane di(meth)acrylate, 1,4-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane Aliphatic (meth)acrylic acid ester compounds having a low molecular weight (molecular weight less than 1000), such as nandiol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerin tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; dioxane glycol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, Examples of the ether-containing (meth)acrylic acid ester compound include low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylic acid ester compounds such as 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, and propoxylated bisphenol A di(meth)acrylate; low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylic acid ester compounds such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; and high molecular weight (molecular weight 1000 or more) acrylic acid ester compounds such as (meth)acrylic-modified polyphenylene ether resin.Examples of commercially available (meth)acrylic radically polymerizable compounds include "A-DOG" (dioxane glycol diacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd., "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dioxane glycol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic-modified polyphenylene ether) manufactured by SABIC Innovative Plastics.

[0120] The styrene radical polymerizable compound is, for example, a compound having one or more, preferably two or more, vinyl groups directly bonded to an aromatic carbon atom. Examples of the styrene radical polymerizable compound include low molecular weight (molecular weight less than 1000) styrene compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; high molecular weight (molecular weight 1000 or more) styrene compounds such as vinylbenzyl-modified polyphenylene ether resin and styrene-divinylbenzene copolymer. Examples of commercially available styrene-based radically polymerizable compounds include "ODV-XET(X03)", "ODV-XET(X04)", and "ODV-XET(X05)" (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemical & Material Co., Ltd., and "OPE-2St 1200" and "OPE-2St 2200" (vinylbenzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Co., Inc.

[0121] The allyl radical polymerizable compound is, for example, a compound having one or more, preferably two or more, allyl groups. Examples of allyl radical polymerizable compounds include aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, and diallyl 2,3-naphthalenecarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; epoxy-containing aromatic allyl compounds such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; benzoxazine-containing aromatic allyl compounds such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; and allyl silane compounds such as diallyl diphenyl silane. Commercially available allyl radical polymerizable compounds include, for example, "TAIC" (1,3,5-triallyl isocyanurate) manufactured by Nippon Kasei Chemical Industry Co., Ltd., "DAD" (diallyl diphenate) manufactured by Nisshoku Techno Fine Chemical Co., Ltd., "TRIAM-705" (triallyl trimellitate) manufactured by Wako Pure Chemical Industries, Ltd., trade name "DAND" (2,3-naphthalene carboxylate diallyl) manufactured by Nippon Distillation Industry Co., Ltd., "ALP-d" (bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane) manufactured by Shikoku Kasei Corporation, "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd., and "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Kasei Corporation.

[0122] The maleimide radical polymerizable compound is, for example, a compound having one or more, preferably two or more, maleimide groups. The maleimide radical polymerizable compound may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or an aromatic maleimide compound containing an aromatic amine skeleton. Commercially available maleimide radical polymerizable compounds include, for example, "SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd., "BMI-1500", "BMI-1700", "BMI-3000J", "BMI-689", and "BMI-2500" (dimer diamine structure-containing maleimide compounds) manufactured by Designer Molecules, Inc., "BMI-6100" (aromatic maleimide compound) manufactured by Designer Molecules, "MIR-5000-60T" and "MIR-3000-70MT" (biphenylaralkyl-type maleimide compounds) manufactured by Nippon Kayaku Co., Ltd., "BMI-70" and "BMI-80" manufactured by K.I. Chemical Industry Co., Ltd., and "BMI-2300" and "BMI-TMH" manufactured by Daiwa Kasei Kogyo Co., Ltd. In addition, as the maleimide-based radically polymerizable compound, a maleimide resin (maleimide compound containing an indane ring skeleton) disclosed in the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211 may be used.

[0123] The ethylenically unsaturated bond equivalent of the radical polymerizable compound (H) is preferably 20 g / eq. to 3000 g / eq., more preferably 50 g / eq. to 2500 g / eq., further preferably 70 g / eq. to 2000 g / eq., and particularly preferably 90 g / eq. to 1500 g / eq. The ethylenically unsaturated bond equivalent represents the mass of the radical polymerizable compound per equivalent of the ethylenically unsaturated bond.

[0124] The weight average molecular weight (Mw) of the radical polymerizable compound (H) is preferably 40000 or less, more preferably 10000 or less, further preferably 5000 or less, and particularly preferably 3000 or less. The lower limit is not particularly limited, but may be, for example, 150 or more.

[0125] The content of the (H) radical polymerizable compound in the resin composition may be 0% by mass or more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 1.0% by mass or more, and is preferably 16% by mass or less, more preferably 12% by mass or less, particularly preferably 8.0% by mass or less, assuming that the non-volatile components in the resin composition are 100% by mass.

[0126] The content of the (H) radical polymerizable compound in the resin composition may be 0% by mass or more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.10% by mass or more, and particularly preferably 1.0% by mass or more, and is preferably 25% by mass or less, more preferably 20% by mass or less, and particularly preferably 15% by mass or less, based on the resin component in the resin composition being 100% by mass.

[0127] 10.(I) Optional Additives The resin composition according to this embodiment may further contain (I) any additive as an optional non-volatile component in addition to the above-mentioned components (A) to (H). (I) Examples of optional additives include radical polymerization initiators such as peroxide-based radical polymerization initiators and azo-based radical polymerization initiators; thermosetting resins other than epoxy resins such as epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, benzoxazine resins, unsaturated polyester resins, phenolic resins, melamine resins, and silicone resins; organic fillers such as rubber particles; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers. antioxidants such as hindered phenol antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic acid anhydride-based stabilizers. (I) The optional additives may be used alone or in combination of two or more kinds.

[0128] [11. (J) Solvent] The resin composition according to the present embodiment may further contain a (J) solvent as an optional volatile component in combination with the non-volatile components such as the above-mentioned components (A) to (I). As the (J) solvent, an organic solvent is usually used. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of suitable solvents include ether ester solvents such as ethyl acetate, ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide solvents such as dimethyl sulfoxide, nitrile solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (J) Solvents may be used alone or in combination of two or more.

[0129] The content of the (J) solvent is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, or it can be 0 mass%.

[0130] [12. Method for producing resin composition] The resin composition according to the present embodiment can be produced, for example, by mixing the above-mentioned components. The above-mentioned components may be mixed partially or entirely at the same time, or may be mixed in sequence. In the process of mixing each component, the temperature may be appropriately set, and thus heating and / or cooling may be performed temporarily or throughout. In addition, stirring or shaking may be performed in the process of mixing each component.

[0131] [13. Physical properties of resin composition] The resin composition according to the present embodiment can provide a cured product with excellent smear removability. For example, when the smear removability is evaluated under the conditions described in the section of [Evaluation method of smear removability and arithmetic average roughness (Ra)] in the examples described later, the maximum smear length of the smear extending from the wall surface at the bottom of the via hole can be made less than 5 μm. In general, the shorter the maximum smear length, the better the smear removability.

[0132] The resin composition according to the present embodiment can provide a cured product with excellent plating adhesion. That is, when a conductor layer is formed on a cured product of the resin composition by plating, the conductor layer and the cured product can have high adhesion. For example, when the plating peel strength is measured under the conditions described in the section "Method of measuring plating adhesion (plating peel strength)" in the examples described later, the plating peel strength can be increased. The plating peel strength indicates the magnitude of the force required to peel off the conductor layer formed on the cured product of the resin composition by plating, and the higher the plating peel strength, the better the plating adhesion. The plating peel strength is preferably 0.45 kgf / cm or more, more preferably 0.50 kgf / cm or more, and particularly preferably 0.53 kgf / cm or more.

[0133] The resin composition according to the present embodiment can provide a cured product having excellent metal foil adhesion. That is, when the resin composition is laminated on a metal foil and cured to form a cured product, the metal foil and the cured product can have high adhesion. For example, when the copper foil peel strength is measured under the conditions described in the section [Method of evaluating metal foil adhesion] in the examples described later, the copper foil peel strength can be increased. The copper foil peel strength represents the magnitude of the force required to peel the copper foil as the metal foil from the cured product of the resin composition, and the higher the copper foil peel strength, the better the metal foil adhesion. The copper foil peel strength is preferably 0.50 kgf / cm or more, more preferably 0.60 kgf / cm or more, and particularly preferably 0.70 kgf / cm or more.

[0134] The resin composition according to the present embodiment can usually give a cured product with a low dielectric loss tangent. For example, when the dielectric loss tangent of the cured product is measured under the conditions described in the section [Method of measuring dielectric loss tangent] in the examples described later, a low dielectric loss tangent can be obtained. The dielectric loss tangent of the cured product is preferably 0.0040 or less, more preferably 0.0035 or less, and particularly preferably 0.0030 or less.

[0135] The cured product of the resin composition according to this embodiment can usually have a small surface roughness when roughening treatment is performed. For example, when the arithmetic mean roughness Ra of the cured product after roughening treatment is measured under the conditions described in the section [Method of evaluating smear removability and arithmetic mean roughness (Ra)] in the examples described later, a small arithmetic mean roughness Ra can be obtained. The arithmetic mean roughness Ra is preferably 120 nm or less, more preferably 110 nm or less, and particularly preferably 100 nm or less. There is no particular restriction on the lower limit, and it can be 30 nm or more, 40 nm or more, etc.

[0136] [14. Uses of resin composition] The resin composition according to the present embodiment can be used as a resin composition for insulating purposes, and can be particularly preferably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer). For example, the resin composition according to the present embodiment can be used as a resin composition for forming an insulating layer of a printed wiring board, and can be preferably used as a resin composition for forming an interlayer insulating layer (resin composition for interlayer insulation).

[0137] The resin composition according to the present embodiment may be used as a resin composition for forming a rewiring formation layer (resin composition for forming a rewiring formation layer). The rewiring formation layer refers to an insulating layer for forming a rewiring layer. The rewiring layer refers to a conductor layer formed on the rewiring formation layer as an insulating layer. For example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition according to the present embodiment may be used as a resin composition for forming a rewiring formation layer. When a semiconductor chip package is manufactured through the following steps (1) to (6), a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0138] Furthermore, the resin composition according to the present embodiment can be used in a wide range of applications in which a resin composition is used, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulating material, a hole filling resin, and a component embedding resin.

[0139] [15. Sheet-type laminated materials] The resin composition according to the present embodiment may be used by coating in the form of a varnish, but from an industrial perspective, it is preferable to use the resin composition in the form of a sheet-like laminate material containing the resin composition.

[0140] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.

[0141] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support. The resin composition layer is formed of the resin composition according to the present embodiment. Thus, the resin composition layer usually includes a resin composition, and preferably includes only the resin composition.

[0142] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but may be 5 μm or more, 10 μm or more, etc.

[0143] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0144] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0145] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0146] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0147] As the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0148] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0149] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer.

[0150] The resin sheet can be produced, for example, by preparing a liquid (varnish-like) resin composition as is or by dissolving the resin composition in a solvent to prepare a liquid (varnish-like) resin composition, applying this onto a support using a die coater or the like, and then drying to form a resin composition layer.

[0151] The solvent may be the same as the solvent explained as a component of the resin composition. The solvent may be used alone or in combination of two or more.

[0152] Drying may be performed by heating, blowing hot air, or the like. Drying conditions are not particularly limited, but drying is performed so that the content of the solvent in the resin composition layer is usually 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the solvent in the resin composition, for example, when a resin composition containing 30% by mass to 60% by mass of a solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0153] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it is usually possible to use the resin sheet by peeling off the protective film.

[0154] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition according to this embodiment.

[0155] The sheet-like fiber substrate used for the prepreg may be, for example, a commonly used substrate for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, and is usually 10 μm or more.

[0156] The prepreg can be produced by a method such as a hot melt method or a solvent method.

[0157] The thickness of the prepreg can be in the same range as that of the resin composition layer in the resin sheet described above.

[0158] The sheet-like laminate material can be suitably used for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be even more suitably used for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).

[0159] [16. Printed wiring boards] The printed wiring board according to one embodiment of the present invention includes an insulating layer containing a cured product obtained by curing the resin composition according to the present embodiment. The printed wiring board can be manufactured, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing the resin composition layer to form an insulating layer.

[0160] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the above-mentioned "inner layer substrate". When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0161] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0162] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.

[0163] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0164] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0165] The support may be removed between step (I) and step (II) or after step (II).

[0166] In step (II), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition. The resin composition layer is usually cured by thermal curing. Specific curing conditions for the resin composition layer may be the conditions usually adopted when forming an insulating layer for a printed wiring board.

[0167] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time may be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0168] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 150° C., preferably 60° C. to 140° C., more preferably 70° C. to 130° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0169] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art that are used in manufacturing printed wiring boards. When the support is removed after step (II), the removal of the support may be carried out between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer in steps (I) to (V) may be repeated to form a multilayer wiring board, as necessary.

[0170] In another embodiment, the printed wiring board can be manufactured using the above-mentioned prepreg. The manufacturing method can be basically the same as when a resin sheet is used.

[0171] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole may be appropriately determined depending on the design of the printed wiring board.

[0172] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0173] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using a swelling liquid can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0174] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0175] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0176] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0177] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0178] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0179] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0180] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method. From the viewpoint of ease of production, the semi-additive method is preferred. Below, an example of forming the conductor layer by the semi-additive method is shown.

[0181] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0182] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.

[0183] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.

[0184] [17. Semiconductor Devices] A semiconductor device according to an embodiment of the present invention includes the above-mentioned printed wiring board. The semiconductor device can be manufactured using the printed wiring board.

[0185] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES

[0186] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to these examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. In addition, the temperature and pressure conditions were room temperature (25°C) and atmospheric pressure (1 atm), unless otherwise specified.

[0187] [Example 1] Eight parts of a biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.) and two parts of a naphthalene type epoxy resin ("HP-4032-SS" manufactured by DIC Corporation, 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) were heated and dissolved in 15 parts of solvent naphtha with stirring. This was cooled to room temperature to prepare a dissolved composition of the epoxy resin.

[0188] To this epoxy resin solution, 40 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of approximately 223 g / eq., toluene solution with non-volatile content of 65%) and spherical silica (Admatechs Corporation's "SO-C2", average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573") were added. 2 / g) 120 parts, biphenyl skeleton-containing acrylic acid ester (Shin-Nakamura Chemical Co., Ltd. "A-LEN-10", (meth)acryloyl group equivalent approx. 268 g / eq.) 4 parts, triazine skeleton-containing phenol-based hardener (DIC Corporation "LA-3018-50P", active group equivalent approx. 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) 2 parts, carbodiimide-based hardener (Nisshinbo Chemical Co., Ltd. "V-03" A resin composition was prepared by mixing 5 parts of a toluene solution with an active group equivalent of approximately 216 g / eq. and a non-volatile content of 50%, 0.1 parts of an imidazole curing accelerator ("1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd., 1-benzyl-2-phenylimidazole), and 2 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass) and dispersing the mixture uniformly using a high-speed rotating mixer.

[0189] [Example 2] Instead of 40 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62 mass%) was used. In addition, instead of 4 parts of a biphenyl skeleton-containing acrylic acid ester (Shin-Nakamura Chemical Industry Co., Ltd.'s "A-LEN-10", (meth)acryloyl group equivalent of about 268 g / eq.), 4 parts of a biphenyl skeleton-containing acrylic acid ester (Honshu Chemical Industry Co., Ltd.'s "A-BP-2EO") was used. A resin composition was prepared in the same manner as in Example 1 except for the above.

[0190] [Example 3] The amount of biphenyl type epoxy resin (Nippon Kayaku's "NC3000L", epoxy equivalent of about 269 g / eq.) was changed from 8 parts to 10 parts. In addition, naphthalene type epoxy resin (DIC's "HP-4032-SS", 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) was not used. Furthermore, instead of 40 parts of active ester compound (DIC's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of active ester compound (DIC's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass) was used. In addition, the amount of the biphenyl skeleton-containing acrylic acid ester ("A-LEN-10" manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acryloyl group equivalent: about 268 g / eq.) was changed from 4 parts to 8 parts. Except for the above, the resin composition was prepared in the same manner as in Example 1.

[0191] [Example 4] Biphenyl-type epoxy resin (Nippon Kayaku's "NC3000L", epoxy equivalent of about 269 g / eq.) was not used. The amount of naphthalene-type epoxy resin (DIC's "HP-4032-SS", 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) was changed from 2 parts to 10 parts. Furthermore, instead of 40 parts of active ester compound (DIC's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of active ester compound (DIC's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass) was used. In addition, the amount of the biphenyl skeleton-containing acrylic acid ester ("A-LEN-10" manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acryloyl group equivalent weight: about 268 g / eq.) was changed from 4 parts to 2 parts. Except for the above, the resin composition was prepared in the same manner as in Example 1.

[0192] [Example 5] Instead of 40 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62 mass%) was used. In addition, 4 parts of a biphenylaralkyl novolac type maleimide compound (Nippon Kayaku Co., Ltd.'s "MIR-3000-70MT", MEK / toluene mixed solution with non-volatile content of 70%) were added to the resin composition. A resin composition was prepared in the same manner as in Example 1 except for the above items.

[0193] [Example 6] Instead of 40 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62 mass%) was used. In addition, 4 parts of methacrylic modified polyphenylene ether (SABIC Innovative Plastics' "SA9000-111") were added to the resin composition. A resin composition was prepared in the same manner as in Example 1 except for the above items.

[0194] [Example 7] Instead of 40 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass) was used. In addition, 4 parts of vinylbenzyl-modified polyphenylene ether (Mitsubishi Gas Chemical Corporation's "OPE-2St 2200", toluene solution with non-volatile content of 65%) was added to the resin composition. A resin composition was prepared in the same manner as in Example 1 except for the above items.

[0195] [Comparative Example 1] Biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.) was not used. In addition, the amount of naphthalene type epoxy resin ("HP-4032-SS" manufactured by DIC Corporation, 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) was changed from 2 parts to 10 parts. Furthermore, 10 parts of acrylic acid ester ("A-DOG" manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acryloyl group equivalent of about 156 g / eq.) was used instead of 4 parts of biphenyl skeleton-containing acrylic acid ester ("A-LEN-10" manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acryloyl group equivalent of about 268 g / eq.). A resin composition was prepared in the same manner as in Example 1 except for the above.

[0196] [Comparative Example 2] The amount of biphenyl type epoxy resin (Nippon Kayaku's "NC3000L", epoxy equivalent of about 269 g / eq.) was changed from 8 parts to 10 parts. In addition, naphthalene type epoxy resin (DIC's "HP-4032-SS", 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) was not used. Furthermore, instead of 40 parts of active ester compound (DIC's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of active ester compound (DIC's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass) was used. Also, instead of 4 parts of a biphenyl skeleton-containing acrylic acid ester ("A-LEN-10" manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acryloyl group equivalent of about 268 g / eq.), 5 parts of an acrylic acid ester ("DCP-A" manufactured by Kyoeisha Chemical Co., Ltd., (meth)acryloyl group equivalent of about 152 g / eq.) were used. Furthermore, 4 parts of a biphenyl aralkyl novolac type maleimide compound ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., MEK / toluene mixed solution with non-volatile content of 70%) were added to the resin composition. Except for the above, the resin composition was prepared in the same manner as in Example 1.

[0197] [Comparative Example 3] The amount of biphenyl type epoxy resin (Nippon Kayaku's "NC3000L", epoxy equivalent of about 269 g / eq.) was changed from 8 parts to 10 parts. In addition, naphthalene type epoxy resin (DIC's "HP-4032-SS", 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) was not used. Furthermore, instead of 40 parts of active ester compound (DIC's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 40 parts of active ester compound (DIC's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass) was used. In addition, a biphenyl skeleton-containing acrylic acid ester ("A-LEN-10" manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acryloyl group equivalent weight: about 268 g / eq.) was not used. A resin composition was prepared in the same manner as in Example 1 except for the above.

[0198] [Preparation of resin sheet] A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin compositions obtained in the Examples and Comparative Examples were uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet including a support and a resin composition layer. The resin sheet thus obtained was used to perform evaluations by the following method.

[0199] [Evaluation method for smear removal and arithmetic mean roughness (Ra)] <Preparation of evaluation board A> (1) Surface preparation for interior boards: A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") with copper foil on the surface was prepared as an inner layer substrate. The copper foil on the surface of this inner layer substrate was etched with a microetching agent (Mec "CZ8101") with a copper etching amount of 1 μm to perform a roughening treatment. Then, it was dried at 190°C for 30 minutes.

[0200] (2) Lamination and curing of resin sheets: The resin sheets obtained in the above-mentioned Examples and Comparative Examples were laminated on both sides of the inner layer substrate using a batch-type vacuum pressure laminator (a two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was bonded to the inner layer substrate. This lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds.

[0201] The laminated resin sheet was then heat-pressed at atmospheric pressure at 100°C and a pressure of 0.5 MPa for 60 seconds to smooth it. It was then placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 170°C and heated for 30 minutes. The resin composition layer was thermally cured by these heating steps, and an insulating layer was obtained as a cured layer made of the cured product of the resin composition.

[0202] (3) Formation of via holes: Using a CO2 laser processing machine (Via Mechanics' "LK-2K212 / 2C"), the insulating layer was processed under the conditions of a frequency of 2000Hz, a pulse width of 3μs, an output of 0.95W, and a shot number of 3, to form a via hole penetrating the insulating layer. The top diameter (diameter) of the via hole on the insulating layer surface was 50μm, and the diameter of the via hole on the insulating layer bottom surface was 40μm. After that, the support was peeled off to obtain an intermediate substrate having a layer structure of insulating layer / inner layer substrate / insulating layer.

[0203] (4) Roughening treatment: The intermediate substrate was immersed in a swelling solution, Swelling Dip Securigant P (manufactured by Atotech Japan), at 60°C for 10 minutes. Next, it was immersed in a roughening solution, Concentrate Compact P (aqueous solution of KMnO4: 60g / L, NaOH: 40g / L) (manufactured by Atotech Japan), at 80°C for 20 minutes. Finally, it was immersed in a neutralizing solution, Reduction Solution Securigant P (manufactured by Atotech Japan), at 40°C for 5 minutes. The obtained substrate was designated as evaluation substrate A.

[0204] <Evaluation of smear removal> The periphery of the bottom of the via hole of the evaluation substrate A was observed with a scanning electron microscope (SEM). From the image obtained by the observation, the maximum smear length extending from the wall surface of the bottom of the via hole was measured and evaluated according to the following criteria. "○": Maximum smear length is less than 5 μm. "X": maximum smear length is 5 μm or more.

[0205] <Measurement of arithmetic mean roughness (Ra)> The arithmetic mean roughness Ra of the insulating layer surface of evaluation substrate A was measured using a non-contact surface roughness meter (Beeco Instruments' "WYKO NT3300") in VSI mode with a 50x lens over a measurement range of 121 μm × 92 μm. Measurements were performed at 10 randomly selected points, and the average values ​​were calculated and shown in the table below.

[0206] [Method of measuring plating adhesion (plating peel strength)] <Preparation of evaluation board B> Evaluation substrate A was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. After heating at 150°C for 30 minutes to perform an annealing treatment, an etching resist was formed, and after forming a pattern by etching, copper sulfate electroplating was performed to form a plating conductor layer with a thickness of 30 μm. Next, an annealing treatment was performed at 200°C for 60 minutes, and the obtained substrate was designated evaluation substrate B.

[0207] <Measurement of peel strength of plated conductor layer> A cut was made in the plating conductor layer of evaluation board B in a portion not including the via hole, surrounding an area 10 mm wide and 150 mm long. One end of this portion was peeled off and held with the grip of a tensile tester (Autocom type tester "AC-50C-SL" manufactured by TSE Corporation). It was pulled vertically at a speed of 50 mm / min at room temperature (25°C), and the load [kgf / cm] when 100 mm was peeled off was measured as the plating peel strength.

[0208] [Method of measuring dielectric tangent] The resin sheets obtained in each Example and Comparative Example were thermally cured at 190°C for 90 minutes, and the support was peeled off to obtain a sheet-like cured product. The cured product was cut to obtain a test piece with a width of 2 mm and a length of 80 mm. The dielectric tangent (tan δ) of this test piece was measured at a measurement frequency of 5.8 GHz by the cavity resonance method using a cavity resonator perturbation method dielectric constant measuring device "CP521" manufactured by Kanto Applied Electronics Development Co., Ltd. and a network analyzer "E8362B" manufactured by Agilent Technologies. Measurements were performed on two test pieces, and the average value was calculated.

[0209] [Metal foil adhesion evaluation method] The metal foil adhesion was evaluated by measuring the copper foil peel strength according to the following procedure.

[0210] <Creating an evaluation board> (1) Copper foil preparation: The shiny side of an electrolytic copper foil (Mitsui Mining & Metals Co., Ltd. "3EC-III", thickness 35 μm) was etched by 1 μm with a micro-etching agent (Mech Co., Ltd. "CZ8101") to roughen the copper surface, and then anti-rust treatment (CL8300) was performed. The copper foil whose surface was etched with the micro-etching agent in this way may be referred to as "CZ copper foil" hereinafter. Furthermore, this copper foil was heat-treated in an oven at 130°C for 30 minutes to obtain copper foil I having a roughened treated surface.

[0211] (2) Preparation of inner layer board: A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, Panasonic "R1515A") was prepared, which had copper foil on its surface and an inner layer circuit formed thereon. Both sides of this glass cloth-based epoxy resin double-sided copper-clad laminate were etched to a thickness of 1 μm with a microetching agent (Mec "CZ8101") to roughen the copper foil surface. This resulted in an inner layer substrate having a CZ copper foil with a treated surface on its surface.

[0212] (3) Lamination of resin composition layer: The resin sheets prepared in the examples and comparative examples were laminated on both sides of the inner layer substrate. This lamination was performed using a batch-type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was in contact with the inner layer substrate. The lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet was heat-pressed at 100°C and a pressure of 0.5 MPa for 60 seconds. Thereafter, the support was peeled off to expose the resin composition layer.

[0213] (4) Lamination of copper foil and curing of resin composition layer: The treated surface of the copper foil I was laminated on the exposed resin composition layer under the same conditions as in "(3) Lamination of the resin composition layer" above. The resin composition layer was then cured at 200°C for 90 minutes to form an insulating layer containing a cured product of the resin composition. Through the above operations, an evaluation substrate C was obtained in which CZ copper foil was laminated on both sides of the insulating layer. This evaluation substrate C had a layer structure of copper foil I / insulating layer / inner layer substrate / insulating layer / copper foil I.

[0214] <Measurement of copper foil peel strength> Evaluation board C was cut into small pieces of 150 mm x 30 mm. A cutter was used to make a cut in the small piece of copper foil I, surrounding a section of 10 mm width and 100 mm length. One end of this section was peeled off and held with the grip of a tensile tester (Autocom universal testing machine "AC-50C-SL" manufactured by TSE Corporation). The load [kgf / cm] when 35 mm was peeled off by pulling vertically at a speed of 50 mm / min at room temperature (25°C) was measured as the copper foil peel strength. The measurement was performed in accordance with the Japanese Industrial Standard JIS C6481.

[0215] [result] The results of the above-mentioned Examples and Comparative Examples are shown in the table below.

[0216] [Table 1]

[0217] [Table 2]

[0218] In the examples, it has been confirmed that even when components (E) to (H) are not contained, the same results as those in the above examples are obtained, although to a lesser extent.

Claims

1. A resin composition comprising (A) an epoxy resin, (B) an active ester compound, (C) an inorganic filler, and (D) a (meth)acrylic acid ester having a biphenyl skeleton, When the non-volatile components in the resin composition are taken as 100% by mass, the content of the active ester compound (B) is 10% by mass or more, When the non-volatile components in the resin composition are taken as 100% by mass, the content of the inorganic filler (C) is 60% by mass or more, A resin composition, in which a mass ratio W D / (W A +W B ) of a total mass W A +W B of (A) an epoxy resin and (B) an active ester compound in the resin composition to a mass W D of (D) a (meth)acrylic acid ester having a biphenyl skeleton is 0.05 or more.

2. The resin composition according to claim 1 , wherein the (D) (meth)acrylic acid ester having a biphenyl skeleton includes a compound containing an ether structure.

3. The resin composition according to claim 1 or 2, wherein the (D) (meth)acrylic acid ester having a biphenyl skeleton includes a compound represented by the following formula (D1): 【Chemistry 1】 (In formula (D1), R 11 each independently represents a hydrogen atom or a methyl group; R 12 each independently represents a divalent aliphatic hydrocarbon group, m1 represents an integer of 0 to 5; n1 represents an integer of 0 to 6; R 21 each independently represents a hydrogen atom or a methyl group; R 22 each independently represents a divalent aliphatic hydrocarbon group, m2 represents an integer of 0 to 5; n2 represents an integer of 0 to 6. However, m1+m2 is 1 or more.)

4. The resin composition according to any one of claims 1 to 3, wherein the content of the (D) (meth)acrylic acid ester having a biphenyl skeleton is 0.5 mass% or more and 25 mass% or less, based on 100 mass% of non-volatile components in the resin composition.

5. The resin composition according to any one of claims 1 to 4, further comprising one or more (E) curing agents selected from the group consisting of phenol-based curing agents and carbodiimide-based curing agents.

6. The resin composition according to any one of claims 1 to 5, further comprising (F) a curing accelerator.

7. The resin composition according to any one of claims 1 to 6, further comprising a thermoplastic resin (G).

8. The resin composition according to any one of claims 1 to 7, which is for forming an insulating layer.

9. A cured product of the resin composition according to any one of claims 1 to 8.

10. A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 8.

11. A resin sheet comprising a support and a resin composition layer formed on the support from the resin composition according to any one of claims 1 to 8.

12. A printed wiring board comprising an insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 8.

13. A semiconductor device comprising the printed wiring board according to claim 12.

Citation Information

Patent Citations

  • Circuit connecting material, connecting method using the same, and connection structure

    JP2012041541A

  • Resin material and multilayer printed board

    JP2020023714A

  • Resin composition

    JP2021075650A

  • Resin composition

    JP2021134300A

  • Resin composition

    JP2021172756A